Hairy B-cell lymphoproliferative disorder and its differential diagnosis: a case with long-term follow-up - Kensuke Matsuda; Yosuke Matsumoto; Mihiko Yoshida; Kazuho Shimura; Hiroto Kaneko; Tohru Inaba; Shigeo Horiike; Junya Kuroda; Masafumi Taniwaki (Mediterranean Journal of Hematology and Infectious Diseases)
Hairy B-cell lymphoproliferative disorder (HBLD) is one of chronic polyclonal B-cell lymphocytosis. We report a 47-year-old female Japanese patient diagnosed as having HBLD based on lymphocytosis with hairy cell appearance and characteristic phenotypes including CD11c+, and without B-cell monoclonalities. She was a non-smoker, and possessed HLA-DR4. She has been closely followed up without treatment and lymphoma development for over five years. Although this disease is quite rare and has been reported, to our knowledge, in only 13 Japanese cases, an accurate diagnosis, particularly differential diagnosis from persistent polyclonal B-cell lymphocytosis or hairy cell leukemia-Japanese variant is essential for the prevention of unnecessary treatments.